An electronic analog multiplier - Lazo, Danilo C. (1965)
The design and construction of an electronic analog multiplier was undertaken to provide the analog computer of the College of Engineering, University of the Philippines with a compatible multiplier to increase its capabilities; provide experience data on the development of balancing bridge modulators, symmetrical clampers and multivibrators; and evaluate the performance of a time divition multiplier circuit. The circuit used are not new and there is no claim to originality. However, the information on the troubles encountered during the design and development of the multiplier, the design criterion and test techniques used, as well as the steps done to remedy the trouble may serve as guide to future work on similar circuits and to evolve a systematic procedure in the design and development of these circuits.